2014
DOI: 10.1177/194008291400700111
|View full text |Cite
|
Sign up to set email alerts
|

Movement and Activity Pattern of a Collared Tigress in a Human-Dominated Landscape in Central India

Abstract: Tigers (Panthera tigris) are wide-ranging species, and a permeable landscape matrix outside Protected Areas (PAs) is extremely important for their dispersal. A tigress which had fallen in a water duct in the Nagpur district was rescued by the Forest Department on 12 th October, 2011 and released on 27 th November, 2011 in a forest adjacent to the site of capture. A GPS-GSM collar that we fitted on her indicated that she remained in the same forest area until 25 th December, 2011, and then moved eastwards into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 27 publications
(35 reference statements)
0
16
0
Order By: Relevance
“…Given that the tiger is a secretive and elusive species, understanding such behavioural responses is highly challenging, unless equipped with suitable monitoring tools, such as radio or GPS telemetry. There has not been many previous studies which could utilize such technological inputs and where it was attempted, except for the long-term study carried out in Chitwan National Park during the 1980s (Sunquist 1981;Smith 1993); sample sizes had always been low, constraining data quality and interpretations (Seidensticker 1976(Seidensticker , 2010Chundawat 1997;Chundawat et al 2016;Karanth and Sunquist 2000;Smith 1984;Sankar et al 2010;Barlow et al 2011;Athreya et al 2014;Sharma et al 2010Sharma et al , 2011Chakravarty 2009;Majumder et al 2012;Schaller 2009). Dispersal events to a new environment reflect the ability of the animals to implement decision process linked to fitness (Smith 1993).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Given that the tiger is a secretive and elusive species, understanding such behavioural responses is highly challenging, unless equipped with suitable monitoring tools, such as radio or GPS telemetry. There has not been many previous studies which could utilize such technological inputs and where it was attempted, except for the long-term study carried out in Chitwan National Park during the 1980s (Sunquist 1981;Smith 1993); sample sizes had always been low, constraining data quality and interpretations (Seidensticker 1976(Seidensticker , 2010Chundawat 1997;Chundawat et al 2016;Karanth and Sunquist 2000;Smith 1984;Sankar et al 2010;Barlow et al 2011;Athreya et al 2014;Sharma et al 2010Sharma et al , 2011Chakravarty 2009;Majumder et al 2012;Schaller 2009). Dispersal events to a new environment reflect the ability of the animals to implement decision process linked to fitness (Smith 1993).…”
Section: Discussionmentioning
confidence: 97%
“…These included one telemetry (Goodrich et al 2010) and four snow tracking studies (Matyushkin 1978;Poddubnaya and Kovalev 1993;Salkina 1993;Yudakov and Nikolaev 1987) on Amur tigers; 12 telemetry-based studies (Seidensticker 1976;Sunquist 1981Sunquist , 2010Chundawat 1997;Chundawat et al 1999;Karanth and Sunquist 2000;Smith 1984;Sankar et al 2010;Barlow et al 2011;Athreya et al 2014;Sharma et al 2011;Chakravarty 2009;Majumder et al 2012), one camera trap-based study (Sharma et al 2010) and one field observation-based home range study (Schaller 2009) on Indian tiger; three radio telemetry-based (Report ZSL 2003;Priatna et al 2012;Maddox et al 2007) and one camera trap-based projects (Franklin et al 1999) on Sumatran tigers. Majority of these studies (18 studies) estimated home ranges based on 100 % MCP, while only few studies adopted other methods for home range estimations (three studies with 95 % MCP and two studies with 95 % FK methods).…”
Section: Home Range Comparison With Other Studiesmentioning
confidence: 99%
“…Our results are supported by empirical data on tiger movement. Recent data from radio-collared tigers reveals that long distance dispersing tigers do not avoid agriculture-village matrix and cross low traffic roads (Athreya et al . 2014; Krishnamurthy et al .…”
Section: Discussionmentioning
confidence: 99%
“…Tigers are habitat generalists (ranging from 0-3000 meters above sea level), their occurrence is associated with forests in the CIL and they have been reported to avoid desserts and short grasslands (Kitchener and Dugmore 2000, Yumnam et al 2014). Athreya et al . (2014) revealed that tigers disperse through and use less rugged areas in Central India.…”
Section: Methodsmentioning
confidence: 99%
“…The current understanding of tigers in India is based on protected areas, where human activity is restricted (Athreya et al 2014). Knowledge of how tigers use areas outside the protected areas is not available and creates uncertainty regarding the tigers' use of forests with human presence and activity.…”
Section: Introductionmentioning
confidence: 99%